Determination of Trace Tetracycline Using Phase-Separation Sublation and Ultraviolet Detection - Hou, Yanmin; Xie, Jimin (Asian Journal of Chemistry, 2013)
A novel analytical method was proposed to determine trace tetracycline (TC) by phase-separation sublation using Mg(II) as a ligand. When pH is 7.0, tetracycline and Mg(II) can combine to a stable complex (Mg-TC). Under certain conditions, the complex can be separated from a solution by phase-separation sublation, because it has better hydrophobicity, this procedure estimated by HPLC was good. The optimum phase-separation floatation was performed. 3.5 mol L-1 sodium chloride as ion intensity regulator, caustic soda solution as acidity regulator and tetrahydrofuran as extraction solvent. The detection wavelength is 380 nm, linear regression equation is A = 1.912 × 105C + 0.011, linear range is from 1.7 × 10-7 to 1.02 × 10-5 mol L-1, floating rate is 89 %, enrichment multiple is 26.7. The recoveries of tetracycline in water was 96.1 to 98.2 %.